Effect of High Temperatures on Biological Performance ofTrogoderma granarium (Everts) (Coleoptera: Dermestidae) - Baghdad Science Journal (مجلة بغداد للعلوم, 2007)
The effect of three high temperatures for five exposure periods on the developments of larvae, pupae and adults of Trogoderma granarium (Everts) and their biological performance were investigated. The results revealed that the percent of mortality was increased as the temperature and the exposure period increased, e. g. exposing last instar larvae to 45°C for 6 hrs caused 100% death of this stage, while exposing adults (1-3) days old to the same temperature and exposure time resulted in that these adults did not able to survive more than 24 hrs.; in addition, the results showed that the ability of reproduction of adults was depended on the temperature, duration of exposure and the sex.